Underground Hydro-Pumped Energy Storage Using Coal Mine Goafs: System Performance Analysis and a Case Study for China - Jiang, Deyi; Chen, Shao; Liu, Wenhao; Ren, Yiwei; Guo, Pengyv; Li, Zongze (Frontiers in Earth Science, 2021)
In response to the Paris climate agreement, the Chinese government has taken actions to improve the energy structure by reducing the share of coal-fired thermal power and increasing the use of clean energy. However, due to the extreme shortage of large-scale energy storage facilities, the utilization efficiency of wind and solar power remains low. This paper proposes to use abandoned coal mine goafs serving as large-scale pumped hydro storage (PHS) reservoir. In this paper, suitability of coal mine goafs as PHS underground reservoirs was analyzed with respects to the storage capacity, usable capacity and ventilation between goaf and outside. The performance of the proposed goaf-PHS system was analyzed based on the reservoir estimation and meteorological information from a typical region in China. It has been found that using abandoned coal mine goafs to develop PHS plants is technically feasible in wind and solar-rich northwestern and southwestern China.